Aplikasi Teori Gelombang Elliott dalam Memprediksi Pergerakan Harga di Pasar Saham - Zahra, Annisa; Chandra, Cindy; Nurfarida, Risma (CV. Kalimasada Group, 2023)
Stock Trend Prediction is a complex matter as their movements constantly fluctuate and are affected by many factors such as political elements, world economic situation, investor expectations and psychological factors. One way to analyze stock prices is technical analysis. This method focuses on indicators and stock patterns that are formed. Elliott Wave is a technical analysis method. This study shows an approach based on a combination of artificial neural networks and Elliott wave theory that will predict the likely direction of future trends. The conclusion of this research is that combining Elliott wave theory and Fibonacci can be an effective and profitable strategy for trading on the stock market. This combination has demonstrated high accuracy and can increase trading returns. This combination still offers profits, even when the stock declines.